Apply the same rules to variables as you do numbers.
For 3a - a, you subtract 1a from 3a to get 2a. And 7 - 7 = 0, so your first question is 2a.
In terms of combing like terms, think of numbers as saying, "2 ones."
So, your second question, -3x - 1 - 5x + 4 can be expressed as, "-3x minus 1 one minus 5x plus 4 ones." When you group them together, you get:
-3x - 5x - 1 + 5 = -8x + 4
Incidentally, it is usually good practice to factor these out. If your teacher doesn't care about that, then worry about it later. Assuming your teacher wants it, then you can divide 4 or -4 out of the answer to get:
-8x + 4 = 4(-2x + 1) OR = -4(2x - 1)
Do keep in mind that you can write subtraction as the addition of negative numbers. So, -3x - 5x can also be written as -3x + (-5x), which is how I got -8x.
A final thing to remember is the distribution rule. You multiply before you add. So your last question is:
6(2t - 3) + 3(t + 5)
You distribute first to get:
12t - 18 + 3t + 15
Also written as:
12t + 3t + (-18) + 15 <== think of them as -18 ones and 15 ones, if necessary.
You can add them together to get:
15t - 3
Again, if you need to factor it, you'll get:
3(5t - 1)
Hopefully, that's enough to get you started.
2007-01-12 06:40:19
·
answer #1
·
answered by Rev Kev 5
·
0⤊
0⤋
First, use the distributive property to multiply out where possible.
Then, combine like terms...which means add (or subtract) all terms with the same variable. Set equation equal to 0 (zero). Isolate the variable to solve for it. This should give you a good start...
3a+7-a-7=?
*2a
2a = 0 (The 7's cancel out & 3a - 1a is 2a.)
a = 0 (Divide both sides by 2.)
----------
-3x – 1 – 5x + 4?
*-8x+3
-8x+3 - 3 = 0 -3 subtract -3 both sides
-8x/-8 = -3/-8 divide by -8 on both sides
x = 3/8 (neg over neg is pos.)
-----------
-4(n + 1) – (n + 2)?
-4n - 4 - n - 2
*-5n - 6
--------------
4b – (9b – 8)?
4b - 9b + 8
*-5b + 8
----------------
2(y + 1) + 2(y – 2)?
2y + 2 + 2y - 4
*4y - 2
------------
-5(y – 2) – 7y?
-5y + 10 - 7y
*-12y +10
--------------
6(2t – 3) + 3(t + 5)?
12t - 18 +3t +15
*15t - 3
----------
If you just need simplifaction, stop at the starred answers...
2007-01-12 06:53:04
·
answer #2
·
answered by SusanB 5
·
0⤊
0⤋
You're not looking for solutions, but for simplification.
There are two principles you need to learn here. I'll give you a couple freebies to get you a running start.
-3x -1 -5x +4
Gather up the x's, get them away from the numbers without x's.
(-3x + -5x) + (-1 + 4)
Now add them up!
-8x +3
is your answer.
Next is distribution across parentheses.
4b - (9b - 8)
To make it easier, let's put a "1" right here:
4b - 1(9b - 8)
it doesn't change the outcome of the problem, but it does help to visualize that you are multiplying by a number, not just a minus sign!
You have to multiply the -1 by 9b, and then subtract from that -1 * 8. How i like to do it is to change the - on the outside to a +, and reverse all of the signs inside the parentheses. It makes it simpler for me.
4b + 1(-9b + 8)
Now, multiply each number in the parentheses by 1, and break the parentheses.
4b - 9b + 8
Again, gather up the variables ("b" this time) and get them away from the constants (numbers without variables).
(4b - 9b) + 8
-5b + 8
is your answer.
Good luck with the rest of them! (unless somebody comes along and just jots down all the answers, you lazy bum.)
2007-01-12 06:45:26
·
answer #3
·
answered by John C 4
·
0⤊
0⤋
3a + 7 - a - 7 =
3a - a + 7 - 7 =
2a
- - - - - - - - - - - -
- 3x - 1 - 5x + 4
- 3x - 5x - 1 + 4
- 8x + 3
- - - - - - - - - --
- 4(n + 1) - (n + 2
- 4n - 4 - n - 2
- 4n - n - 4 - 2
- 5n - 6
- - - - - - - -
4b - (9b - 8) =
4b - 9b + 8
- 5b + 8
- - - - - - - -
2(y + 1) + 2(Y - 2) =
2y + 2 + 2y - 4
2y + 2y + 2 - 4
4y - 2
- - - - - - - -
- 5(y - 2) - 7y =
- 5y + 10 - 7y =
- 5y - 7y + 10
- 12y + 10
- - - - - - -
6(2t - 3) + 3(t + 5) =
12t - 18 + 3t + 15
12t + 3t - 18 + 15
15t - 3
- - - - - - - -s-
2007-01-12 07:25:04
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
0⤋
Hmmm, I have the sneaking suspicion this is your algebra homework that you're looking for someone to do for you, so I'm not going to do that. But I will get you started.
The first thing you want to do is get rid of the parentheses, which you do by multiplying whatever comes before it by each term inside it. So, for example, if you had 2(x-5), you would get 2x-10 because you're taking first the 2 times the x, then the 2 times the negative 5. If there is no actual number in front of the parentheses, assume there is an invisible 1 there and multiply everything inside by whatever sign is outside. So if you had
5-(x+3), you would get 5-x-3. (I assume you know that a positive times a positive number is positive, a negative times a negative is positive, and a negative times a postive is negative.)
After you've gotten rid of the parentheses, then you combine like terms. So for example, if you have something like:
4x + 3 - 2x - 1
You would combine all the terms with x and then combine all the whole numbers. So you would get:
2x - 2 (Because 4x - 2x = 2x, and 3 - 1 = 2.)
Once you've combined all the like terms, you're done!
Now, if they ask you to actually solve for x (or whatever letter they're using) there are a few more steps after this. Let me know if that's the case.
2007-01-12 07:00:34
·
answer #5
·
answered by CrysV 5
·
0⤊
0⤋
Slope-intercept type: y = mx + b, the place m is the slope and b is the y-intercept a million.) The slope is 4, so which you already understand the equation so a approaches is y = 4x + b. Now replace the component (a million, -2) for x and y into the equation so which you will remedy for b: y = 4x + b (replace a million for x and -2 for y) -2 = 4(a million) + b -2 = 4 + b -6 = b answer: y = 4x - 6 2.) returned, the slope is 3, so its equation so a approaches is y = 3x + b. remedy for b with tips from substituting the component (5, -3) for x and y into the equation: y = 3x + b -3 = 3(5) + b -3 = 15 + b -18 = b answer: y = 3x - 18 3.) comparable factor... y = -3x + b 0 = -3(-3) + b 0 = 9 + b -9 = b answer: y = -3x - 9 4.) This time the slope is undefined, meaning the line is vertical. whilst the slope is undefined, the equation of the line is immediately x = ?. The x-coordinate of the component (7, 8) is 7, so the equation of the line is purely x = 7. answer: x = 7
2016-10-07 01:37:25
·
answer #6
·
answered by lashbrook 4
·
0⤊
0⤋
3a + 7 - a - 7
= 2a
-3x - 1 - 5x + 4
= 3 - 8x
-4(n + 1) - (n + 2)
= -4n - 4 - n - 2
= -5n - 6
4b - (9b - 8)
= 4b - 9b + 8
= 8 - 5b
2(y + 1) + 2(y - 2)
= 2y + 2 + 2y - 4
= 4y - 2
-5(y - 2) - 7y
= -5y + 10 - 7y
= 10 - 12y
6(2t - 3) + 3(t + 5)
= 12t - 18 + 3t + 15
= 15t - 3
2007-01-12 06:42:37
·
answer #7
·
answered by Tom :: Athier than Thou 6
·
0⤊
2⤋
3a+7-a-7=2a = (3-1)a +(7-7)
use same combine-the-terms approach on other Qs
2007-01-12 06:40:18
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋
2a
-8x + 3
-5n - 2
-5b + 8
4y - 2
-12y + 10
15t - 3
2007-01-12 07:00:49
·
answer #9
·
answered by dinh nguyen 1
·
0⤊
0⤋
1) 2a
2) -8x + 3
3) -5n + -2
4) -5b - 8
5) 4y + -2
6) -12y - 2
7) 15t - 3
I better get best ans after that that took me 5 mins!!!
2007-01-12 06:40:44
·
answer #10
·
answered by neutreno 3000 2
·
0⤊
2⤋